Analysis of Non-Point Source (NPS) Pollutant Load and Water Capacity of Bolango River, Gorontalo Province - Yetti Mosi; Fitryane Lihawa; Marike Mahmud; Ferry Novrizal (Postgraduate, University of Mataram, 2024)
This study analyzes the non-point source (NPS) pollution load and water carrying capacity of the Bolango River in Gorontalo Province, Indonesia. The river is experiencing water quality degradation due to various human activities, particularly in the upstream and midstream regions. Water samples were collected at six locations along the river during five different periods, with key parameters such as pH, Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Nitrate (NO₃), Total Phosphate (TP), and Total Suspended Solids (TSS) measured. A simulation model, Qual2KW Version 5.1, was employed to estimate the river’s carrying capacity and validate the pollutant load. Results show that TSS levels frequently exceed regulatory limits, particularly in downstream segments, with the highest concentration recorded at 645 mg/L. BOD and COD levels remained within acceptable limits, although some points demonstrated high values due to agricultural and domestic waste discharge. The findings suggest that pollution control strategies should focus on managing agricultural runoff, domestic wastewater, and solid waste, particularly in critical segments of the watershed. Immediate intervention is needed to address the TSS exceedances and mitigate further environmental degradation. This study provides important insights for developing sustainable watershed management practices for the Bolango River